If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
x = (2/3)*y // - (2/3)*y
x-((2/3)*y) = 0
x+(-2/3)*y = 0
x-2/3*y = 0 // + -2/3*y
x = -(-2/3*y)
x = 2/3*y
x = 2/3*y
| 3x+4-x=2+x+1 | | 3u+8=56 | | 2/3y=x | | 2x+10=x-3 | | 2z-5=5z-4z | | 4-12+j=2+8 | | 181-5x=31x+17 | | 3/4x-1/2x=1/3x+2 | | 5x+2=2(x+4) | | 3m+5(3-m)=3-4m | | 9t^2-8t+(16/9) | | 10x^2-4=3x | | y=2x-1/2 | | 10x^2=15-7x | | 1/5=y+2/5 | | (3x+14)/2=4 | | 5x+2=1(x+4) | | x/4=y+2 | | 35*7k/4 | | -5+10=16x-4-15x | | 12x+2=1(x+4) | | 8.6+4.1(x)=x+77.9 | | 4y-1=2+1 | | .05*.05*.05*.05= | | -5(4t-2)+7t=8t-6 | | 8.6+4.1x=x+77.9 | | 12x-2=1(x+4) | | -8=(x+68)/-9 | | 8a-3(a-4)=3 | | 12x-2=1(x-3) | | 2x+7=3x-2 | | (3x+7)/4=-2 |